1993
DOI: 10.1042/bj2890561
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CoA and acyl-CoAs on GTP-dependent Ca2+ release and vesicle fusion in rat liver microsomal vesicles

Abstract: (1) CoA (IC50 23 microM) and acyl-CoAs (IC50 values 15-18 microM) inhibit GTP-dependent vesicle fusion in rat liver microsomal vesicles. Acyl-CoAs of carbon chain length C8 and C20 are much less effective than acyl-CoAs of carbon chain length C14-C18. The effect of CoA is mimicked by dephospho-CoA, but not by desulpho-CoA. High acyl-CoA concentrations (50 microM) appear to favour formation of small vesicles (budding), while 50 microM CoA does not. (2) Low concentrations of CoA (EC50 2 microM) and palmitoyl-CoA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…values ranging from 15 to 18 µM for C "% -, C "' -and C ") -CoA esters, whereas high acylCoA concentrations (50 µM) favoured the formation of small microsomal vesicles [65]. The authors suggested that GTPinduced membrane fusion in rat liver microsomes depends on an as yet unknown acylation\deacylation mechanism required for complete vesicle sealing.…”
Section: Long-chain Acyl-coa Esters In Signal Transduction Membrane Tmentioning
confidence: 95%
See 1 more Smart Citation
“…values ranging from 15 to 18 µM for C "% -, C "' -and C ") -CoA esters, whereas high acylCoA concentrations (50 µM) favoured the formation of small microsomal vesicles [65]. The authors suggested that GTPinduced membrane fusion in rat liver microsomes depends on an as yet unknown acylation\deacylation mechanism required for complete vesicle sealing.…”
Section: Long-chain Acyl-coa Esters In Signal Transduction Membrane Tmentioning
confidence: 95%
“…In liver, in contrast with muscle, low concentrations of acylCoA suppressed GTP-and inositol 1,4,5-trisphosphate-induced Ca# + release from rat liver microsomal vesicles, and caused re-uptake of Ca# + into and enlargement of the inositol 1,4,5-trisphosphate-sensitive compartment [65,81].…”
Section: Acyl-coa Regulation Of Ion Fluxesmentioning
confidence: 99%
“…(Benedetti et al, 1988), and therefore a sensitization by glucagon to Ins(1,4,5)P3-dependent agonists can be envisaged. The effect on the Ins(1,4,5)P3-insensitive Ca2+ pool also could contribute to the termination of the effect of Ins(1,4,5)P3-dependent agonists by reaccumulating released Ca2+ (Benedetti et al, 1986 Lee, 1989) and the increase in acyl-CoA cellular content (Comerford and Dawson, 1993 (1985) examining glucagon-induced Ca2+ fluxes in rat hepatocytes was carried out with 24-h-starved animals and the data appear qualitatively similar to those obtained by others using hepatocytes from fed animals. On the other hand, Rashed and Patel (1987) found that in 24-h-fasted animals, glucagon failed to induce 45Ca efflux, but that induced by phenylephrine was unaffected.…”
Section: Other Ca2+ Flux-related Signals Generated By Glucagonmentioning
confidence: 99%
“…and that, in a substantially longer period following the GTPinduced interaction, fusion between different vesicular components of the ER may take place (7,16,22,23). Since, in permeabilized cells, a small component of the ER appears to exist as non-intact vesicular membranes, the rapid transfer process induced by GTP results in the fast release of a substantial proportion of the accumulated Ca 2ϩ (7,16), as observed in Fig.…”
Section: Fatty Acid-mediated Ca 2ϩ Sequestrationmentioning
confidence: 80%
“…Work by Comerford and Dawson (22,23) has suggested that GTP-induced Ca 2ϩ movements may reflect the activation of fusion between membranes. Instead, we have interpreted our results to indicate that the rapid fluxes of Ca 2ϩ observed in response to GTP reflect a process that may precede a subsequently activated membrane fusion event (16,24).…”
Section: Intracellular Camentioning
confidence: 99%